2000
DOI: 10.1038/sj.bjp.0703058
|View full text |Cite
|
Sign up to set email alerts
|

Differential actions of L‐cysteine on responses to nitric oxide, nitroxyl anions and EDRF in the rat aorta

Abstract: 1 The e ects of L-cysteine were tested in rat aortic rings on responses to nitric oxide free radical (NO . ), nitroxyl (NO 7 ) derived from Angeli's salt and endothelium-derived relaxing factor (EDRF) activated by acetylcholine, ATP and the calcium ionophore A23187. Concentrations of 300 mM or less of L-cysteine had no e ect on responses. 2 Relaxations produced by exogenous NO . (0.25 ± 2.5 mM) were markedly prolonged and relaxations produced by sodium nitroprusside (0.001 ± 0.3 mM) were enhanced by 1 and 3 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
90
2
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 41 publications
14
90
2
2
Order By: Relevance
“…Endogenous and exogenous thiols are often used in studies involving • NO and/or H 2 S signaling pathways (Stamler 1994;Ellis et al 2000;Gaston et al 2006;Duan and Chen 2007;Li et al 2009;Yong et al 2010Yong et al , 2011Kasparek et al 2012). Our results may suggest that in these studies, a possible modulation of H 2 S-induced…”
Section: Biological Significancementioning
confidence: 57%
See 1 more Smart Citation
“…Endogenous and exogenous thiols are often used in studies involving • NO and/or H 2 S signaling pathways (Stamler 1994;Ellis et al 2000;Gaston et al 2006;Duan and Chen 2007;Li et al 2009;Yong et al 2010Yong et al , 2011Kasparek et al 2012). Our results may suggest that in these studies, a possible modulation of H 2 S-induced…”
Section: Biological Significancementioning
confidence: 57%
“…• NO and H 2 S signaling pathways (Stamler 1994;Ellis et al 2000;Gaston et al 2006;Duan and Chen 2007;Li et al 2009;Yong et al 2010;Yong et al 2011;Kasparek et al 2012). For instance, thiols such as Cys, NAC and GSH have been reported to influence the • NO-H 2 S effects on myocyte contraction (Yong et al 2010(Yong et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Like NO ⅐ , NO Ϫ induces vasodilation in vivo and in vitro in association with the formation of iron-nitrosyl complexes and the conversion of NO Ϫ to NO ⅐ (11-13). These effects are highly sensitive to redox state, being effectively eliminated by the addition of reduced thiols (13,14) or copper-containing enzymes (15). Whether and how NO Ϫ affects the intact heart itself remains unknown, but this too might be anticipated to display marked redox sensitivity.…”
mentioning
confidence: 99%
“…It has been suggested that HNO can affect the etiology of various pathophysiological conditions such as inflammation and neurodegenerative diseases, especially when H 2 O 2 and transition metal ions are present (6,7). Similar to NO ⅐ and NO ϩ , HNO is a potent inducer of the antioxidant protein heme oxygenase 1 (8), exhibits vasorelaxant properties (9), and modulates the activity of thiol-containing proteins, such as aldehyde dehydrogenase (10,11) and the N-methyl-D-aspartate receptor (12,13). In in vivo experiments, Paolocci et al (14) observed that HNO exerts positive inotropic and lusitropic action, which unlike NO ⅐ and nitrates is independent and additive to ␤-adrenergic stimulation and increases the release of plasma calcitonin gene-related peptide; these results suggest that donors of HNO are potential prodrugs for the treatment of heart failure (14).…”
mentioning
confidence: 99%